EUROPEIZACJA ADMINISTRACJI PUBLICZNEJ - Lipowicz, Irena (Wydział Prawa i Administracji UAM, 2008)
Europeisation of public administration may be equally a subject of an analysis in the course of administrative law or administration as well as management. A characteristic feature of the recent years, however, has been a theoretical departing of the two approaches, leading to major practical consequences. The paper discusses the main normative, structural and functional aspects of the Europeisation of administration at the national and Community level. It also shows the main (fundamental) legal and administrative consequences of Europeisation of administration in Poland, and the effects o f the gradual development of common European administration. Special attention has been given the theoretical clash of the so-called classical community method with the idea of new governance and its main form existing in the Community - an open coordination method. What is particularly interesting is that the functioning o f the rapidly developing network administration and the growing number o f EU agencies, all have relatively feeble legal grounds in the treaty, a fact that has been criticised since long ago. Moreover, contrary to the expectations, neither the draft of the European Constitution, nor the Reforming Treaty, have changed much in that respect.
EUROPEISATION OF PUBLIC ADMINISTRATION